Synthesis and characterization of high-quality activated carbons from hard-shelled agricultural wastes mixture by zinc chloride activation - Akcakal, Ozlem; Sahin, Mehmet; Erdem, Mehmet (Taylor & Francis Inc, 2019)
In this study, a mixture apricot and peach stones, and almond shell, which are hard-shelled agricultural wastes, was evaluated as a precursor for activated carbon synthesis. Effects of the impregnation and pyrolysis conditions on ACs synthesis were investigated. The ACs were characterized by surface area, pore size, pore volume, surface functional groups by Boehm's titration and FTIR analysis, ash content, pH(pzc), and SEM-EDX. It has been found that the impregnation conditions and pyrolysis temperature have important effect on the microspores formation. ACs having specific surface area in the range of 1,125.73-2,073.04 m(2)g(-1) and total pore volumes in the range of 0.5498-1.0918 cm(3) g(-1) can be synthesized from the mixture activated by ZnCl2 at impregnation ratios of higher than 15/40. These values are higher than those of the most commercial ACs. Therefore, it can be concluded that the mentioned wastes mixture is a promising precursor for producing high-quality ACs.
Keywords: Activated carbon; Chemical activation; Impregnation; Lignocellulosic wastes; Pyrolysis